Proposta de modelo de gestão da fase de manutenção de edifícios, utilizando o conceito BIM, com foco na manutenção preventiva - Rosa, Fabiana Pires (Universidade do Vale do Rio dos Sinos, 2021)
Considered an emerging issue in civil construction, facility management (FM) requires various agents and disciplines to carry out interventions that guarantee buildings' expected durability and performance. However, the lack of formalization of FM, dispersed, disconnected, and incomplete information results in little efficiency and preventive strategy. This study aims to propose a management model for the maintenance phase of buildings, using the BIM (Building information modeling) concept, focusing on preventive maintenance. The study was carried out from a case study, through three stages: FM diagnosis of an educational building (EB) and also of a residential building (RB); FM-BIM integration, and model proposal. The results showed that the EB management, as it has an infrastructure department, FM is carried out formally and with a preventive character. Still, the person responsible for management points out that there is a lack of information. In the RB, FM is performed with a corrective character and with little formalization. In both, the design of the buildings is not used. Through Dynamo software, FM activities were integrated into EB BIM design (Revit model), according to the criteria of frequency and status. The model proposes FM through sub-processes, planning and action and control. Through the FM-BIM integrated model, the building design starts to communicate the maintenance activities according to the adopted criteria visually. According to the perception of those responsible for maintaining the buildings studied, the use of the model greatly facilitates access to information over time. However, it requires that designs are carried out with maintenance information and someone who knows the software used, indicating a greater involvement of the construction company in the condominium segment.
Keywords: Gestão de manutenção; BIM; Construção civil; Manutenção preventiva; Facility management; Civil construction; Preventive maintenance; ACCNPQ::Engenharias::Engenharia Civil